Melemahnya Identitas Lokal di Era Globalisasi: Analisis Faktor, Dampak, dan Strategi Penguatan Berbasis Tinjauan Pustaka Sistematis - Ziyad Arzaq Abdani; Witrinia Fauziyani; Maulidia Rahmah; Zumna Afifatun Nisa; Azahro Isna Mubarok; Elyana Rosyita; Aira Annastasya; Ika Oktavianti (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study examines the weakening of local identity in the era of globalization by analyzing its driving factors, socio-cultural impacts, and reinforcement strategies through a systematic literature review. Global cultural flows, digital media expansion, and shifting social values have increasingly influenced patterns of communication, lifestyle, and cultural expression, particularly among younger generations. The review indicates that globalization contributes to the erosion of traditional practices, local languages, and communal values, while simultaneously reshaping social cohesion and collective identity. The impacts extend beyond cultural loss, affecting character formation, intergenerational transmission of values, and the sustainability of local wisdom. To address these challenges, the study identifies strategic approaches centered on local wisdom–based education, ethnopedagogical practices, family and community engagement, and adaptive use of digital media. Empirical findings from previous studies and official reports demonstrate that integrated and collaborative strategies strengthen cultural awareness and foster a sense of belonging without rejecting modernity. The study concludes that reinforcing local identity requires a holistic framework involving educational institutions, families, communities, media, and public policy, ensuring that local culture remains a dynamic foundation for social resilience in a globalized world.